Learning Behavior in Establishing Student Personality Competencies in 2nd Grade of State Elementary School 5 Sungai Raya - Mariyati Teluma (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
The problems studied are: 1) What is the class II student's learning behavior in classroom/face-to-face learning activities? 2) How is the Student's learning behavior in a structured activity? 3) How are students' learning behaviors in their own activities? 4) What is the student's personality competence that is formed from the learning behaviors they have done so far. The method used is descriptive qualitative, using research instrument: observation of participant/participant observation, interview, and documentation. The sample of this research is four informant of the second-grade student, second semester, that is GL, US, ML, AR. The findings of this study explain that the learning behavior of second-grade students of SD Negeri 5 Kecamatan Sungai Raya Kabupaten Kubu Raya in the learning activities in class II based on curriculum system 13 (K 13), has been done according to the standard of learning process in the class, but not yet maximal. The Personality of the Class II Student is seen in dynamic conditions, in the process of forming according to the period of development that occurred in his time, with the GL details lacking enthusiasm in following the lesson, US diligent and passionate even though he was less intelligent in learning, ML quiet but diligent, and AR is diligent and passionate but likes to be noisy in the classroom, nevertheless the development of their personality. including enough categories, in terms of self-esteem, respect for other people's opinions, courtesy, and cooperation they display in interacting with their peers.